1993
DOI: 10.1093/jac/31.suppl_e.73
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of azithromycin and amoxycillin in paediatric patients with acute otitis media

Abstract: In this open study, a three-day regimen of azithromycin (single daily dose of 10 mg/kg) was compared with a ten-day regimen of amoxycillin paediatric suspension (30 mg/kg/day in three divided doses; children > 20 kg received 250 mg tid daily) in 154 children (aged 2-12 years) with a clinical diagnosis of acute otitis media (13 recurrent). Full clinical, bacteriological and laboratory safety assessments were performed during and after the study. Of the 77 azithromycin patients, 61 (79%) were considered cured, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…48,53,54,57,60,69,70,73 Cointervention was permitted in 38% of trials, usually with analgesics and decongestants. [46][47][48]50,51,53,57,59,[64][65][66] In 2 trials, myringotomy had been conducted in early treatment failures. 48,59 Concurrent use of a second antibiotic was seen in 1 trial.…”
Section: Methodologic Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…48,53,54,57,60,69,70,73 Cointervention was permitted in 38% of trials, usually with analgesics and decongestants. [46][47][48]50,51,53,57,59,[64][65][66] In 2 trials, myringotomy had been conducted in early treatment failures. 48,59 Concurrent use of a second antibiotic was seen in 1 trial.…”
Section: Methodologic Qualitymentioning
confidence: 99%
“…The 32 trials were distributed in antibiotic groups as follows: 17 were short-acting antibiotics, 26,46-58 4 were ceftriaxone sodium, 59-62 and 11 were azithromycin. [63][64][65][66][67][68][69][70][71][72][73] Two of the trials were in a language other than English.…”
Section: Literature Search and Trial Inclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] The same total dose of azithromycin may also be given over 3 days to treat AOM, and several studies have demonstrated clinical equivalence between once-daily azithromycin (10 mg/kg daily) for 3 days and 10-day multidose regimens of amoxicillin, amoxicillin/clavulanate, clarithromycin, and cefaclor. [20][21][22][23][24][25][26][27] Pukander and Rautianen 28 measured total middleear fluid concentrations of azithromycin in children with AOM who received a 10-mg/kg dose on day 1 followed by a 5-mg/kg dose on day 2. Total mean azithromycin concentrations at 24 and 48 hours after the initial dose were 8.61 and 9.43 µg/mL, respectively.…”
Section: A17mentioning
confidence: 99%
“…Azithromycin has been used in pediatric patients for a variety of infections and found to have a lower side effect profile, low rate of discontinuation of therapy caused by side effects, and a low potential for interaction, as well as clinical efficacy similar to that of oral agents such as amoxicillin-clavulanate (1,15,16,22,24) and amoxicillin (17). However, the definition of satisfactory clinical response varied from study to study.…”
Section: Discussionmentioning
confidence: 99%